Changes in Essential Oil Content and Composition of Peppermint (Mentha piperita L.) in Responses to Nitrogen Application - M Seif Sahandi; H Naghdi Badi; A Mehrafarin; F Khalighi-Sigaroodi; M Sharifi (Institue of Medicinal Plants, ACECR, 2019)
Background: Nitrogen is the most important nutrient requirement for plants. Nitrogen supplying affected the leaf area, carbon fixation, glandular trichomes formation, ATP and NADPH content which resulted to the terpenoids biosynthesis enhancement and essential oils accumulation. Objective: This study was aimed to evaluate changes of essential oil content and components by use different levels of Urea fertilizer and its relation with the antioxidant status of peppermint. Method: The two field experiments were conducted on randomized complete block design at 2013 and 2014. The treatments consisted of three levels of nitrogen fertilizer (urea) (0, 75, and 150 kg ha-1). The evaluated traits were included antioxidant enzymes, essential oil percentage and essential oil components. Results: The urea fertilizer had a significant effect (P≤0.01) on the soluble protein amount and antioxidant enzymes activity. Urea consumption in the both years increased the peppermint essential oil content. The interaction of nitrogen fertilizer and year had a significant effect on most of the essential oil components excepted to β-pinene, myrcene, Limonene, 1,8- Cineole, Z-β- Ocimene, and α- Terpineol. Conclusion: Using nitrogen fertilizer increased the peppermint essential oil content. Also, nitrogen deficiency reduced the soluble proteins and essential oil content and in contrast, it increased antioxidant enzymes activity and pulegone content. Therefore, consumption of 75 kg urea per hectare is recommended due to increasing essential oil content, decreasing pulegone rate, and no significant effect on menthol, menthone, and menthofuran contents.